2017
DOI: 10.1016/j.ijnonlinmec.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the acoustic black hole effect by using energy transfer due to geometric nonlinearity

Abstract: International audienceAcoustic Black Hole effect (ABH) is a passive vibration damping technique without added mass based on flexural waves properties in thin structures with variable thickness. A common implementation is a plate edge where the thickness is locally reduced with a power law profile and covered with a viscoelastic layer. The plate displacement in the small thickness region is large and easily exceeds the plate thickness. This is the origin of geometric nonlinearity which can generate couplings be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…1. The effect of this viscoelastic layer can be taken into consideration by using the Ross-Ungar-Kerwin model [1,23], which proposes an expression of the complex bending stiffness D * (x), where () * refers to the complex representation of the term. For an added viscoelastic layer located in the interval [x abh , L], the complex bending stiffness D * (x) writes…”
Section: Modeling Of Added Viscoelastic Layer: Formulation In the Frementioning
confidence: 99%
See 1 more Smart Citation
“…1. The effect of this viscoelastic layer can be taken into consideration by using the Ross-Ungar-Kerwin model [1,23], which proposes an expression of the complex bending stiffness D * (x), where () * refers to the complex representation of the term. For an added viscoelastic layer located in the interval [x abh , L], the complex bending stiffness D * (x) writes…”
Section: Modeling Of Added Viscoelastic Layer: Formulation In the Frementioning
confidence: 99%
“…The idea of using a nonlinear mechanism to transfer energy from low frequencies -where the black hole is ineffective -to high frequencies -where the black hole is very efficient, has emerged recently. Geometric nonlinearity as a mean to realize this transfer has been successfully studied in a previous work [23]. However, the time scale of this mechanism is large as compared to typical periods of the targeted low frequency waves, so that the expected gains remain limited and cannot be obtained immediately.…”
Section: Introductionmentioning
confidence: 99%
“…Further work investigates that NWV < 0.4 is a good rule for designing ABHs [60]. In the study of Denis et al which investigated ABH as a vector for energy transfer from the low frequencies to high frequencies in the framework of nonlinear vibration, a parametric study on a number of beams shown in Figure 43 was developed [61]. Longer additional termination, which means longer LABH, can improve the efficiency of energy transfer.…”
Section: Design Of 1d Abhmentioning
confidence: 99%
“…Krylov indicate that the damping material with higher material loss factor makes the damping effect of the ABH have better performance [29]. Denis et al indicate that a good compromise has been found by using a long additional termination with a moderate length of the damping layer in the framework of nonlinear vibration, which can develop into a turbulent regime [61]. An optimization study was developed by Lee et al [69] and indicates that the damping performance can be enhanced by treating the tip with an appropriate size of damping layer.…”
Section: Design Of Damping Layermentioning
confidence: 99%
See 1 more Smart Citation